Identifying the optimal donor for natural killer cell adoptive therapy to treat paediatric B- and T-cell acute lymphoblastic leukaemia. - Foley, Bree; Ta, Clara; Barnes, Samantha; de Jong, Emma; Nguyen, Michelle; Cheung, Laurence; Buzzai, Anthony; Wagner, Teagan; Wylie, Ben; Fernandez, Sonia; Cruickshank, Mark; Endersby, Raelene; et al. (2020)
Objectives: Natural killer (NK) cells are an attractive source of cells for an 'off the shelf' cellular therapy because of their innate capacity to target malignant cells, and ability to be transferred between donors and patients. However, since not all NK cells are equally effective at targeting cancer, selecting the right donor for cellular therapy is critical for the success of the treatment. Recently, cellular therapies utilising NK cells from cytomegalovirus (CMV)-seropositive donors have been explored. However, whether these NK cells are the best source to treat paediatric acute lymphoblastic leukaemia (ALL) remains unclear.